Exploring the promotion of sexual health literacy for sexually transmitted disease prevention among undergraduate students in Thailand: an ethnographic study - Kreupimy, Sittisak; Boonsawasdgulchai, Peerapong (Universitas Airlangga, 2025)
Introduction: Although previous knowledge has proposed guidelines for promoting sexual health literacy in sexually transmitted disease (STD) prevention, there is a knowledge gap in studies about approaches to promote sexual health literacy for STD prevention among undergraduate students tailored to undergraduate students, who are influenced by specific personal, familial, and sociocultural factors. Methods: This critical ethnographic study explored the promotion of sexual health literacy in STD prevention among undergraduate students in Thailand. The total number of participants was 63 persons, including undergraduate students, health care providers, university department representatives, university administrators, advisors or lecturers, parents, and friends. Data were collected by in-depth interviews, participatory observation, non-participatory observations, field notes, and documented studies. Verify the accuracy of the data using multiple periods, multiple individuals, multiple university departments, member checking, reflexivity, and qualitative research experts. Data were analyzed by thematic analysis. Results: It consists of 2 parts: 1) Development of university mechanisms to prevent, deter, and support students, and 2) Providing health services to care and help for students. Conclusions: The results of this research provide practical knowledge. However, the limitations need to be addressed in the implementation process. Recommendations are that University administrators should increase the integration and promotion of all elements of sexual health literacy to students. Student health centers should develop their competencies in providing counseling services to LGBTQ students. Policymakers should develop specific policies with student participation, and for future research, should explore integration models of all stakeholders and cross-university comparison research.